2019
DOI: 10.3389/fmicb.2019.02058
|View full text |Cite
|
Sign up to set email alerts
|

Cj1388 Is a RidA Homolog and Is Required for Flagella Biosynthesis and/or Function in Campylobacter jejuni

Abstract: Campylobacter jejuni is the leading bacterial cause of acute gastroenteritis worldwide and thus significant to public health. C. jejuni primarily lives in the gastrointestinal tracts of poultry and can contaminate meat during processing. Despite a small genome, the metabolic plasticity of C. jejuni allows proliferation in chicken ceca and mammalian host intestines, and survival in environments with a variety of temperatures, pH, osmotic conditions, and nutrient availabilities. The exact mechanism of C. jejuni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Taken together, the current data suggest that the action of RutC (and potentially RutD) might result in higher nitrogen levels that could be critical for competition in a specific environmental niche. This scenario would be consistent with the emerging model in which the unifying feature of Rid superfamily members is that they accelerate reactions that occur nonenzymatically in vivo ( 4 ). This model further suggests that the RidA subfamily prevents metabolic damage caused by a reactive intermediate ( 16 ), whereas members of other subfamilies increase the efficiency of metabolic processes that might otherwise be constrained by the rate of spontaneous hydrolysis in the cell ( 17 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Taken together, the current data suggest that the action of RutC (and potentially RutD) might result in higher nitrogen levels that could be critical for competition in a specific environmental niche. This scenario would be consistent with the emerging model in which the unifying feature of Rid superfamily members is that they accelerate reactions that occur nonenzymatically in vivo ( 4 ). This model further suggests that the RidA subfamily prevents metabolic damage caused by a reactive intermediate ( 16 ), whereas members of other subfamilies increase the efficiency of metabolic processes that might otherwise be constrained by the rate of spontaneous hydrolysis in the cell ( 17 ).…”
Section: Discussionsupporting
confidence: 84%
“…The exception is the RidA subfamily. All RidA subfamily members tested have enamine deaminase activity ( 3 , 4 , 5 , 6 , 7 ). In Salmonella enterica , and the few other bacteria tested, hydrolysis of the reactive imine intermediate 2-aminoacrylate (2-AA) by RidA prevents metabolic damage that can occur when 2-AA accumulates in vivo .…”
mentioning
confidence: 99%
“…RidA is a broadly conserved member of the large Rid (YjgF/YER057c/UK114) protein superfamily ( 13 ). Members of the RidA subfamily deaminate multiple enamines/imines to the corresponding ketoacids with a faster rate than can be mediated by solution water ( 14 , 15 ). Characterization of a ridA mutant of S. enterica showed that despite its short half-life, 2AA could persist in vivo and partially inactivate certain cellular PLP-dependent enzymes ( 14 , 16 , 17 ).…”
mentioning
confidence: 99%
“…In S. enterica loss of RidA causes serine and cysteine sensitivities, pyruvate excretion, and a motility defect 15,[21][22][23] . Deletion of ridA from Campylobacter jejuni causes defects in motility, autoagglutination and in phage infectivity 24 . Yeast cells lacking the mitochondrial RidA (Mmf1p) exhibit a severe defect in mitochondrial genome stability due to 2AA stress generated by the mitochondrial serine dehydratase inside the organelle 12 .…”
mentioning
confidence: 99%